Desenvolvimento tecnológico e avaliação biológica (in vitro) de produto seco por aspersão obtido a partir da solução extrativa de Hyptis pectinata (L.) Poit (Lamiaceae) (sambacaitá) - Santos, Anderson Ribeiro dos (2015)
Introduction: The Hyptis pectinata L. Poit (Lamiaceae) species is well-known in northeast Brazil as sambacaitá or straw, being used around Sergipe and Alagoas, in the form of tea, for the treatment of gastrointestinal disorders, inflammation, orofacial pain conditions and wound healing. The literature reports low toxicity for the aqueous extract of leaves, besides hepatoprotection and effects antiedematogenic antinociceptive and antioxidant. In parallel to the development of a technologically viable product, the biggest obstacle is the difficulty of defining criteria for evaluating the quality of vegetable raw materials and related products. In this context, this work intent theelaboration of dry product by spraying from a standard extraction solution H. pectinata as well as evaluating the antioxidant and antimicrobial activity.Methods:The extraction solution (SEH) was prepared by decoction of leaves of H. pectinata (L) on a plant scale: solvent of 1.5% (w / v) for 15 minutes. The SEH was spray dried and the resulting product (ESHP) quantified by High Performance Liquid Chromatography Efficiency coupled to Mass Spectrometry (HPLC / MS). After standardizing the ESHP was investigated in model in vitro antioxidant activity and antimicrobial activity in vitro.Results and discussion: The method by HPLC/MS showed excellent performance in the separation of the peaks observing excellent repeatability (RSD <2.0%) and accuracy (rutin>95%). The standard curve for routine was linear with a correlation coefficient greater than 0.9992. In addition to the routine, two other constituents were detected which were identified based on their mass spectra in full scan and retention times of time and compared with literature data available. The concentrations 0.1; 1; 10 and 100 mg/mL were observed that the ESHP inhibited the amount of TBARS formed in a manner similar or superior to compound Trolox (an antioxidant pattern). Furthermore, the ESHP also reduced production of hydroxyl radical as well as nitric oxide production similar or superior to control. The results of disk diffusion test showed a significant difference in the sensitivity of microorganisms against the ESHP (p <0.05). The Minimum Inhibitory Concentration (MIC) of ESHP (312 mg / mL) showed the best performance to inhibit the growth of Gram-positive strains. According to the data collected by this study, H. pectinata presented antioxidant activity in vitro by different mechanisms and antibacterial activity for Gram-positive strains may become alternative therapy for both popular use and for the pharmaceutical industry.